Making Sense Behind the Lens: Closed Circuit Television and the Dutch Customs Office - Arts, Kees; Van Den Berg, Steffie; Lodders, Adinda; Wagenaar, Pieter; De Wit, Daniel (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
Using Goold’s categorization the heuristics of the customs office’s CCTV-operators at Schiphol Airport (Amsterdam, The Netherlands) are mapped. Then, Weick’s sensemaking concept is applied to explain the difference in heuristics – and also in effectiveness - between the two customs office regions studied. It turns out that the inability of one of the regions to apply all of Weick’s properties provides the answer.
Keywords: Netherlands; heuristics; customs office